Compatibilizer Polarity Parameters as Tools for Predicting Organoclay Dispersion in Polyolefin Nanocomposites - Marek Weltrowski; Patricia I. Dolez (Journal of Nanotechnology)
Nanocomposites give an innovative method to increase the mechanical, thermal, and barrier performance of polymers. However, properly dispersing the nanoparticles in the polymer matrix is often key in achieving high performance, especially in the case of hydrophilic nanoparticles and hydrophobic polymers. For that purpose, nanoparticles may be functionalized with organic groups to increase their affinity with the polymer matrix. Compatibilizing agents may also be included in the nanocomposite formulation. This paper aims at identifying parameters relative to the compatibilizer polarity that would allow predicting nanoparticle dispersion in the polymer nanocomposite. The analysis used published data on nanocomposite samples combining clay nanoparticles, polyolefins, and various compatibilizing agents. We studied the correlations between the nanoclay exfoliation ratio and five different parameters describing the compatibilizer hydrophilic-lipophilic balance: the acid value, the mole, and weight fraction of polar groups, the number of polymer chain units per polar group, and the number of moles of polar groups per mole of compatibilizer. The best correlation was observed with the number of polymer chain units per polar group in the compatibilizer. This parameter could be used as a tool to predict the dispersion of organoclay nanoparticles in polyolefins. Another important result of the study is that, among the compatibilizers investigated, those with a low acid value provided a better nanoclay exfoliation compared to those with a high acid value. This may indicate the existence of a maximum in the nanoclay exfoliation/compatibilizer polarity curve, which would open new perspectives for nanocomposite performance optimization.